State Protection and Identification in Hellboy: of reformed devils and other Others in the Pentagon - Maaheen Ahmed (European Journal of American Studies)
This article explores possible implications of the Hellboy comic book series for constructions of individual and national identity in the American context, accounting for the factors of globalization and 9/11 as well as precedents in the comics medium. It also considers Hellboy as a self-reflection on the history and nature of the comics medium itself.